2017
DOI: 10.1080/14686996.2017.1332455
|View full text |Cite
|
Sign up to set email alerts
|

Application of phase-change materials in memory taxonomy

Abstract: Phase-change materials are suitable for data storage because they exhibit reversible transitions between crystalline and amorphous states that have distinguishable electrical and optical properties. Consequently, these materials find applications in diverse memory devices ranging from conventional optical discs to emerging nanophotonic devices. Current research efforts are mostly devoted to phase-change random access memory, whereas the applications of phase-change materials in other types of memory devices ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 190 publications
0
22
0
8
Order By: Relevance
“…Phase‐change random access memory (PCRAM) offers low power consumption, fast switching speeds, and excellent scalability . Recently, it was shown that the switching properties of Ge–Sb–Te based materials used in PCRAM can be further improved by arranging the pseudobinary components Ge–Te and Sb–Te into a superlattice (SL) structure, leading to a significant decrease in switching power consumption .…”
mentioning
confidence: 99%
“…Phase‐change random access memory (PCRAM) offers low power consumption, fast switching speeds, and excellent scalability . Recently, it was shown that the switching properties of Ge–Sb–Te based materials used in PCRAM can be further improved by arranging the pseudobinary components Ge–Te and Sb–Te into a superlattice (SL) structure, leading to a significant decrease in switching power consumption .…”
mentioning
confidence: 99%
“…The popularity of phase-change memories can retrospect to its applications in optical storage devices that mainly serves as the tertiary storage (i.e., off-chip storage) since 1990s [67]. The families of phase-change optical memories that widely adopt the PCMs located in GeTe-Sb 2 Te 3 tie line include rewritable compact disc (CD) [68], rewritable digital versatile disc (DVD) [69], and Blu-Ray [70].…”
Section: Off-chip Storage Memorymentioning
confidence: 99%
“…Scanning probe phase-change memory that comprises a nanoscale electrical probe and a storage stack having a PCM layer sandwiched between a capping layer and a bottom electrodes [93], [94], as illustrated in Figure 11, was proposed to compete with the magnetic hard disk for next generation mass storage device. The recording of phase-change probe memory is performed by injecting write current into the PCM layer via a conductive probe, and the resulting joule heating gives rise to the required phase-transformation.…”
Section: Phase-change Memoriesmentioning
confidence: 99%
“…The write process is achieved by thermally inducing the phase transformation via high write current, and sensing the resistance difference between phase-transformed region and its surrounding can realize the readout process. Updated and Reprinted with permission from [93], [94]. more relies on the conductive diameter of the electrical probe than its physical diameter.…”
Section: Phase-change Memoriesmentioning
confidence: 99%